OPTIONS FOR SELECTION OF ANESTHETICS FOR PAIN RELIEF IN DENTISTRY - Ortikova Nargiza Khairullayevna (Journal of new century innovations, 2024)
Abstract: Local anesthesia in dentistry provides comfort not only for the patient, but also for the doctor, since the planned procedures can be performed in the best possible conditions. It is clear from clinical experience and literature that local anesthesia in dentistry is not always as successful as expected. In particular, mandibular blockage may be difficult or difficult in some patients, even in the absence of a tooth with acute pulpitis. The failure rate for mandibular blockage varies from study to study and teaches us that there is no 100% success rate.